What Can Be Learned About the Economies of China and India from Purchasing Power Comparisons? - Alan Heston (Indian Council for Research on International Economic Relations (ICRIER), 2008)
Comparisons of India and China have been made for over 50 years. This paper focuses on purchasing power estimates in China and India in the 2005 round of the UN International Comparison Programme (ICP) that was coordinated by the World Bank, the Regional Banks and Economic Commissions. The 2005 ICP round provides estimates of purchasing power parities (PPPs) of currencies and real product per capita for 146 countries, and the results for China and India are discussed in the context of the size of these economies. It also provides insights into the prospects of future economic growth in China and India as also policy recommendations for China and the likely scenarios in the future.
Keywords: F4; F41; F43; 330; purchasing power; China; India; economic growth; tertiary sector; capital stock; Wirtschaftswachstum; Entwicklung; Kaufkraft; Vergleich; China; Indien